Adolescents’ Sexuality: The Role of Parent and Microsystem Education of Sexuality - Ayu Arba Zaman; Euis Sunarti; Diah Krisnatuti (Indigenous: Jurnal Ilmiah Psikologi, 2024)
Adolescence is a phase in which a person experiences significant change and maturity in their sexuality. Adolescents seek various sources of knowledge through media access and peers and try to follow their peers' attitudes, values, and behaviour. Religious beliefs and parental interactions are other contributing elements. This research aims to determine the influence of religiosity, sexuality education, references from social media, and peer attachment on sexuality. This research was conducted in Tangerang Regency and involved 180 respondents, consisting of high school, vocational, and madrasah aliyah students in grades 10 and 11, with the criteria of being Muslim, living with both parents and actively using social media. The sampling technique used a stratified non-proportional random sampling method, which was carried out using an interview method using a questionnaire. Adolescents in this study had high religiosity. Sexuality education carried out by fathers is categorized as low, while sexuality education carried out by mothers is categorized as moderate. Adolescents' social media references and peer attachment are categorized as moderate. The results of the Structural Equation Modeling analysis found that religiosity, sexuality education, references from social media, and peer attachment had a significant positive effect on sexuality. These findings imply the importance of interventions that target good and correct values related to sexuality, both in the smallest domain, namely the family, through instilling religious values, sexuality education, and parental control over references in media consumed by adolescents and their peers, as well as more broadly, namely government policy.